OWNERSHIP CONCENTRATION AND EFFECTS OVER FIRM PERFORMANCE: EVIDENCES FROM ITALY - Genc Alimehmeti; Angelo Paletta (European Scientific Journal, ESJ, 2012)
This paper investigates the ownership concentration as a governance mechanism, and its implications over firm value. We conduct an empirical analysis over all Italian listed firm in a four-years period (2006-2009). The results show a positive relationship between ownership concentration and firm value except in 2008, when the results show a non-linear relationship, suggesting that the financial crisis has enhanced the expropriation effects.